Organizational Cynicism, Engagement Climate, and Job Satisfaction: The Mediating Role of Organizational Commitment in Manufacturing Industry Sectors - Qasanah, Fatma Aulia; Irmawati, Irmawati (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the influence of organizational cynicism dimensions and organizational climate engagement on job satisfaction, mediated by organizational commitment across various manufacturing sectors in Indonesia. This study used a quantitative method with a saturated sampling technique involving 100 manufacturing employee respondents. Data were collected using a Likert Scale questionnaire and analyzed using Partial Least Squares (PLS) with the aid of SmartPLS software. The results indicate that organizational engagement has a significant positive effect on job satisfaction and organizational commitment. Furthermore, organizational commitment plays a significant role in mediating the influence of engagement climate on job satisfaction. However, organizational cynicism did not significantly influence job satisfaction or organizational commitment.